Detection of rabies in camel, goat and cattle in Sudan using Fluorescent antibody test (FAT) and hemi nested Polymerase Chain Reaction (hnRT-PCR) - Ahmed, Baraa Abdalaziz; Ali, Yahia Hassan; Ahmed, Omer; Elmagboul, Salma; Ballal, Abdulghader (Journal of Advanced Veterinary and Animal Research, 2016)
Objective: The objective of this study was to identify rabies virus in camels and other animals in Sudan. Materials and methods: Four camel samples were collected from Garraht Elzawia, Kab-kabia and North Darfur areas in Sudan. The samples were collected based on clinical signs. In addition, two camel samples were obtained from Khartoum and Tambool, one goat sample was collected from El-Fashir, and one cattle sample was obtained from Atbara. The samples were transported to the Veterinary Research Institute (VRI) at Khartoum, Sudan for further studies. The samples were subjected for nested and hemi nested RT-PCR (hnRT-PCR) along with the gold standard Fluorescent antibody test (FAT) to diagnose rabies. Results: Out of eight samples, seven were found to be positive by both FAT and RT-PCR methods. The remaining one sample was positive by FAT but negative by hnRT-PCR indicating the suitablity of hnRT-PCR along with FAT for accurate diagnosis of rabies in animals. Conclusion: The study concluded that FAT and RT-PCR are useful tools for research and diagnosis of rabies. http://doi.org/10.5455/javar.2016.c162